Preliminary morphological and phytochemical evaluation of Momordica cochinchinensis spreng - Othman, Halimaton Saadiah; Abdul Rahman, Nor Adilah; Mohamed Nizam, Nor Irdina (Sciendo, 2020)
Momordica cochinchinensis, or Gac fruit belongs to Cucurbitaceae family. Although this species is considered to be native in Southeast Asia especially in Vietnam, Thailand and Laos, it is still contemplated as a rare and new fruit species in Malaysia. Availability of this species is very limited in Malaysia hence, the raw material for researches is also in short supply. Currently, Gac fruit is utilized as traditional food, health supplements, food colouring and juices. Gac fruit was discovered to have high value pharmaceutically and economically as it had been recognized as a rich source of bioactive compounds. On that account, this study aimed to generate preliminary data on the morphological characterisation and phytochemical composition which focused on β-carotene and lycopene content of Gac fruit aril. This data could be useful for further researches particularly on breeding improvement of Gac fruit. The morphological characterisation was mainly based on both vegetative and reproductive parts of the plant. Both β-carotene and lycopene content of aril was analysed and estimated using UV-Vis Spectroscopy technique. The aril was extracted using mixed solvent of n-hexane 95%, ethanol 99.9% and acetone 99% with ratio of 2:1:1 v/v/v. Furthermore, morphological data of root, stem, leaf, flower, fruit and seeds were also successfully recorded. Besides that, the β-carotene and lycopene content obtained were 0.117 ± 0.011 mg/g FW and 0.021 ± 0.002 mg/g FW, respectively. Discrepancy in the results might be due to numerous factors like collection sites, level of maturity at harvest, storage and processing conditions, analysis techniques and type of solvent extractors used that might have affected the quality and contents of the carotenoid. Several suggestions for extension of this study had been propounded so that the benefits of this species could be exploited in the best possible ways.